2008
DOI: 10.1021/jf801668c
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, Gastroprotective, Free-Radical-Scavenging, and Antimicrobial Activities of Hawthorn Berries Ethanol Extract

Abstract: Hawthorn [Crataegus monogyna Jacq. and Crataegus oxyacantha L.; sin. Crataegus laevigata (Poiret) DC., Rosaceae] leaves, flowers, and berries are used in traditional medicine in the treatment of chronic heart failure, high blood pressure, arrhythmia, and various digestive ailments, as well as geriatric and antiarteriosclerosis remedies. According to European Pharmacopoeia 6.0, hawthorn berries consist of the dried false fruits of these two species or their mixture. The present study was carried out to test fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
126
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 55 publications
4
126
2
4
Order By: Relevance
“…Although there is no direct in vivo study to show the anti-inflammatory effect of HBE on AA-induced colitis, its anti-inflammatory and gastroprotective effects have been previously demonstrated in carrageenan-induced rat paw edema and ethanol-induced gastric lesions, respectively. 31 Our analysis, on the other hand, showed that HBE contains considerable amounts of the triterpenic acids OA and UA. We found that OA and UA account for as much as 0.13% and 0.5% of the HBE total content.…”
Section: Discussionmentioning
confidence: 63%
“…Although there is no direct in vivo study to show the anti-inflammatory effect of HBE on AA-induced colitis, its anti-inflammatory and gastroprotective effects have been previously demonstrated in carrageenan-induced rat paw edema and ethanol-induced gastric lesions, respectively. 31 Our analysis, on the other hand, showed that HBE contains considerable amounts of the triterpenic acids OA and UA. We found that OA and UA account for as much as 0.13% and 0.5% of the HBE total content.…”
Section: Discussionmentioning
confidence: 63%
“…Studies revealed, by DPPH method, that the berries have a 1000 times more elevated antioxidant capacity than the quercetine, a powerful antioxidant flavonoid, while the leaves have 10 times more elevated this effect. The antioxidant and lipid lowering effects are due mainly by the high content in flavonoids [3,5,[11][12]. It was proved that the anti-inflammatory effect is due by inhibition of different enzymes and cytokines, like COX2, TNF, IL-1, IL-6 and iNOS [5].…”
Section: Introductionmentioning
confidence: 99%
“…1 Some workers have also reported its role in controlling various diseases like myocardial problem, 2 heart failure, 3 antioxidant, anti-inflammatory and antimicrobial infections. 4,5 It is also used in some other critical disease such as control of central nervous system (CNS), anxiety and depression. 6 A Homeopathic medicine has also been prepared from its flowers and fruits by Homeopathic pharmacopeia of India.…”
Section: Introductionmentioning
confidence: 99%